DESCRIBING CAMTASIA VIDEO AS LEARNING MEDIA: AN ANALYSIS OF RESPONSES IN EFL CONTEXT - Dewi, Ni Kadek Ayu Puspita; Adnyani, Luh Diah Surya; Wahyuni, Luh Gede Eka (International Journal of Language and Literature, 2019)
The use of technology-based learning media, including video in English class can trigger students’ motivation to learn English and improve the learning process. This interesting and innovative media is believed to promote students’ engagement along the process. This descriptive study aims to describe the response of students related to their engagement to the use of English Learning video developed by using Camtasia Studio in second-grade students of elementary school. The data were collected through observations, interview and teacher’s questionnaire. The result reveals that using technology-based media in classroom is really appropriate to increase students’ motivation and learning activeness to get a better teaching and learning process. Students and teacher gave positive responses toward the media and it was categorized into ‘Excellent’ media in which it was interesting and fulfilled the needs of second-grade students. Further, it was suggested for the next research to conduct the study in different grade.